2012
DOI: 10.1186/1471-2458-12-471
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, design and methods for a staggered-entry, waitlist controlled clinical trial of the impact of a community-based, family-centred, multidisciplinary program focussed on activity, food and attitude habits (Curtin University’s Activity, Food and Attitudes Program—CAFAP) among overweight adolescents

Abstract: BackgroundCurrent estimates place just under one quarter of adolescents in Australia as overweight or obese. Adolescence has been identified as a critical period for the development of obesity, yet despite this recognition, there is limited systematic research into or evaluation of interventions for overweight adolescents. Reviews have concluded that there is a substantive evidence gap for effective intervention, but physical activity, lifestyle change and family involvement have been identified as promising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 102 publications
(143 reference statements)
2
16
0
Order By: Relevance
“…This study provides a detailed analysis of physical activity and sedentary time as part of a larger waitlist controlled clinical trial with details previously published. 5,6 Participants completed an 8-week intervention with 12 months of follow-up maintenance intervention. Six assessments were completed: baseline, 3 months following baseline and immediately prior to beginning the intervention (waitlist period for within subject comparison), immediately completing the 8-week intervention (intervention period), and at 3 months, 6 months, and 12 months following the intensive intervention (maintenance periods).…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides a detailed analysis of physical activity and sedentary time as part of a larger waitlist controlled clinical trial with details previously published. 5,6 Participants completed an 8-week intervention with 12 months of follow-up maintenance intervention. Six assessments were completed: baseline, 3 months following baseline and immediately prior to beginning the intervention (waitlist period for within subject comparison), immediately completing the 8-week intervention (intervention period), and at 3 months, 6 months, and 12 months following the intensive intervention (maintenance periods).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…4 One such intervention was Curtin University's Activity, Food, and Attitudes Program (CAFAP), which was a community-based, family-centred lifestyle intervention focused on increasing physical activity and decreasing sedentary behavior and eating behaviors of overweight and obese adolescents. 5 Traditionally, physical activity intervention results have been reported as an overall change in physical activity (total, light, moderate-to-vigorous, and sedentary time) in response to an intervention. In a waitlist controlled clinical trial, participants in CAFAP had limited positive changes in objectively measured physical activity and sedentary behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed protocol for this study has been previously published (Straker et al, 2012). Briefly, the study used a staggered entry, waitlist control design as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Curtin University's Activity, Food and Attitudes Program (CAFAP) was an 8-week community-based, family-centred lifestyle programme for overweight adolescents targeting physical activity, sedentary and nutrition behaviours (Straker et al, 2012 detail (Howie, Olds, McVeigh, Abbott, & Straker, 2015;Straker et al, 2014), with few positive changes in physical activity and body mass index (BMI). Fitness, a set of attributes including cardiorespiratory endurance, muscular strength and endurance, body composition and flexibility is a separate construct from physical activity behaviour with important, independent health implications (Caspersen, Powell, & Christenson, 1985;Myers et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Objectives of the current paper will be accomplished by building on CAFAP's previously described overarching rationale and framework (Straker et al, 2012) to allow for a comprehensive description of theoretical rationale and delivery of behavior-change techniques specific to processes of motivation that are critical for the future development of effective interventions.…”
Section: Objectivesmentioning
confidence: 99%